2022
DOI: 10.36103/ijas.v53i5.1623
|View full text |Cite
|
Sign up to set email alerts
|

Growth, Yield, and Antioxidant Traits of Different Parts of Beetroot as Affected by Vermicompost and Glutathione

Abstract: This study was aimed to assess the impact of vermicompost, glutathione, and their interaction on beetroot (Beta vulgaris L.) growth, yield, and antioxidant traits. The experiment carried out at vegetable field of the College of Agricultural Engineering Sciences - University of Baghdad during fall season 2019. The experiment was conducted using factorial arrangement within Randomized Complete Block Design with two factors and three replicates (3X3X3). Applying vermicompost before cultivation represented the fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 13 publications
0
19
0
Order By: Relevance
“…The results of Table (2)(3)(4) for the cultivar Red, show the superiority of the treatment with fertilizer vermicompost, overlapping with calcium in the number of leaves, the concentration of chlorophyll, the percentage of nitrogen and phosphorous, as it gave 10.56 leaves, 101 mg/100 g, 3.54% and 0.48% respectively. While the treatment with Potassium and silicon increased in the treatment of fertilizer vermicompost overlapping with silicon As it gave 3.28%, 387.67 mg/K.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…The results of Table (2)(3)(4) for the cultivar Red, show the superiority of the treatment with fertilizer vermicompost, overlapping with calcium in the number of leaves, the concentration of chlorophyll, the percentage of nitrogen and phosphorous, as it gave 10.56 leaves, 101 mg/100 g, 3.54% and 0.48% respectively. While the treatment with Potassium and silicon increased in the treatment of fertilizer vermicompost overlapping with silicon As it gave 3.28%, 387.67 mg/K.…”
Section: Resultsmentioning
confidence: 91%
“…One of the basic of healthy nutrition is the production of environmentally safe crops that have a direct impact on the health of individuals, such as the beet crop, which is a natural mine for nutrients which have potassium, iron, zinc, sulfur, copper, silicon, phosphorous, magnesium, nitrates and manganese, as well as vitamins A, B1, B2 , B6 ,C Cellulose, folic acid, carbohydrates, sucrose, glucose, fructose, amino and organic acids [1]. It is also characterized by its richness in medically effective compounds, as beetroot is given with medicines to treat fatty liver, it also has anti-liver poisoning properties Antihepatotoxic because it prevents fats from accumulating in the liver [2], It was also found that the chemical composition of human hemoglobin is similar to the protein found in beet Therefore, it helps to reduce anemia, and increase the rate of hemoglobin in the blood, as well as the high percentage of iron and folic acid which generate red blood cells and also provide the body with pure oxygen, as well as containing several antioxidants Especially in the cortex, such as alpha-lipoic acid B9, which helps lower blood sugar and increases the sensitivity of the pancreas to insulin secretion, Which contributes to overcoming diabetes. Therefore, from previous, it becomes clear the importance of studying the beet crop, as the production of good quality beet roots requires that the growth be regular and balanced between the root and vegetative growth, by providing an organic matter that provide the plant with nutrients and make the soil more capable of retaining moisture and more Disintegration and among these fertilizer is the Vermicompost -the final product of the decomposition of organic matter by some types of earthworms, as it can digest as much as its weight of organic matter daily and produce a high content of nutrients.…”
Section: Introductionmentioning
confidence: 99%
“…(1) Gave highest values of vegetative traits in (0.2vol.vol -1 smoked water+ 75 mg.l -1 zinc) treatment in most vegetative traits as (plant's height, shoots No., main stem diameter, leaves No. ,leaves area distance and percentages of vegetative dry matter) that reaches (104.65 cm, 4.73 shoot.sapling -1 ,9.40 mm, 83.33 leaf.sapling -1 , 28.33 decimeter 2 and 53.70 %) alternatively, superior on other treatments specially at control treatment (0.0 vol.vol -1 smoked water+ 0 mg.l -1 zinc) that given less values reaches (75.00 cm, 3.00 shoot.sapling -1 ,5.96 mm, 47.00 leaf.sapling -1 , 16.13 decimeter 2 and 22.80 %) alternatively, smoke-water increase all growth traits especially when it's interaction with micronutrients application in plants [6]. Results also showed that the treatment (0.2vol.vol -1 smoked water+ 75 mg.l -1 zinc)was superior upon other treatments in root traits (root No., main root diameter, percentages of root dry matter) that gave highest values reaches (7.00 root.sapling -1 , 16.29 mm and 53.70 %) alternatively, while the treatment (0.0 vol.vol -1 smoked water+ 0 mg.l -1 zinc) gave lowest values reaches (3.00 root.sapling -1 , 9.76 mm and 22.80 %) alternatively, according to the table No.…”
Section: Resultsmentioning
confidence: 91%
“…C35 planted in virgin and replant soils , has tolerance to Phytophtora , root rot, Tristeza virus and nematodes, C35 sensitive to some soil like calcareous it's suffering from iron deficiency if planted in this soils, it's has been used to extend the harvest period for navel oranges , but it is slightly higher juice acid content than fruit grown on another rootstocks [5]. .With the world's interest in new technologies for sustainable agricultural development, and due to the presence of a large surplus of agricultural waste that mixed with the soil in order to decompose it to get rid of it, researchers found a traditional application followed in some countries of the old world, which is burning these wastes and mixing them with soil, which leads to an increase of germination rates and improve the vegetative growth of seedlings [6]. [7], found the use of smoke water that derived from different five plant species was affect on vegetative growth of four different plant species .…”
Section: Introductionmentioning
confidence: 99%
“…Yassen et al (36) investigated that spraying Spirulina aqueous extract (2 g.L -1 ) caused increases in growth and yield of lettuce traits. Vermicompost is an economical ecofriendly fertilizer that has proved its effectiveness in various agricultural crops (5,27,30). Vermicompost aqueous extract contains water extractable minerals and hormones that received by plants them (28).…”
Section: Introductionmentioning
confidence: 99%